Detailed computational analysis revealed mutation V210I on PrP induced conformational conversion on β2–α2 loop and α2–α3. Issue 10 (15th August 2016) - Chandrasekaran, P.; Rajasekaran, R.
Abstract : The development of fatal transmissible spongiform encephalopathies (TSE) is associated with the conformational conversion of the normal cellular prion protein, PrP C, into its pathogenic isoform, PrP Sc . Abstract : The development of fatal transmissible spongiform encephalopathies (TSE) is associated with the conformational conversion of the normal cellular prion protein, PrP C, into its pathogenic isoform, PrP Sc . The present study revealed the structural consequences that induce the conversion of PrP C → PrP Sc upon mutation V210I linked with genetic Creutzfeldt–Jakob disease (CJD) using the classical molecular dynamics (MD) approach. Similar to the experimental results, the mutant showed biased disruption in the local folding of α2 and the complete distortion of α3. In addition, substitution of bulkier Ile at position 210 induced reorientations of several residues that were the constituent of hydrophobic cores, thereby influencing α2–α3 inter-helical interactions. In addition, the β2–α2 loop was greatly altered due to the loss of π–π interactions of the residue Tyr 169 with Phe 175, Tye 163, Tyr 162, and Tyr 218, facilitating more conformational flexibility, which may be involved in the conversion of PrP C → PrP Sc . This study afforded a detailed structure and dynamic properties of the mutant, which were consistent with the experimental results, providing an insight into the molecular basis for the conversion of PrP C → PrP Sc, which could be used for the development of antiprion drugs.